Effects of Rope Therapy on Social Attention and Temperament Traits in Autistic Children - Mi Zhou; Kevin Hung; Marco Chun-Cheong Wong; Tony Keng-Tou Chau; Benny Wai-Lun Lam; Cecilia Yuen-Ching Chu; Jialiang Gu; Jiawen Dai; Daniel Hung-Kay Chow (Children, 2025)
Background: Autistic children experience social communication challenges that are often linked to reduced social motivation and attention. However, there is currently no effective intervention to improve social attention in autistic children. Objective: This study compared the effects of rope therapy (RT), a novel intervention, with traditional sensory integration therapy (SIT) on social attention and temperament traits in autistic children. Methods: A two-arm randomized controlled trial was conducted in which participants were randomly assigned to RT (n = 14) and SIT (n = 12) groups. Social attention was assessed using eye-tracking parameters, and temperament trait changes were measured using the Taylor–Johnson Temperament Analysis (T-JTA) scale. Results: Both groups showed significant improvements in social attention over time (p < 0.05). Although the RT group demonstrated numerically greater improvements in social attention compared to the transitional SIT group, most of the between-group differences were not statistically significant. Additionally, the RT group showed significant reductions in anxiety and emotional repression temperament traits (p < 0.05). Conclusions: RT exhibits promise as an effective intervention for improving social attention and temperament trait patterns in autistic children. Further research is required to confirm the findings of this study and explore the long-term effects of RT.